Peanut (Arachis hypogaea) Expressed Sequence Tag Project: Progress and Application. (17th June 2012) - Feng, Suping; Wang, Xingjun; Zhang, Xinyou; Dang, Phat M.; Holbrook, C. Corley; Culbreath, Albert K.; Wu, Yaoting; Guo, Baozhu
Abstract : Many plant ESTs have been sequenced as an alternative to whole genome sequences, including peanut because of the genome size and complexity. The US peanut research community had the historic 2004 Atlanta Genomics Workshop and named the EST project as a main priority. As of August 2011, the peanut research community had deposited 252, 832 ESTs in the public NCBI EST database, and this resource has been providing the community valuable tools and core foundations for various genome-scale experiments before the whole genome sequencing project. These EST resources have been used for marker development, gene cloning, microarray gene expression and genetic map construction. Certainly, the peanut EST sequence resources have been shown to have a wide range of applications and accomplished its essential role at the time of need. Then the EST project contributes to the second historic event, the Peanut Genome Project 2010 Inaugural Meeting also held in Atlanta where it was decided to sequence the entire peanut genome. After the completion of peanut whole genome sequencing, ESTs or transcriptome will continue to play an important role to fill in knowledge gaps, to identify particular genes and to explore gene function.